Effects of Time Budget Pressure, Audit Fee, Independence and Competence on Audit Quality - Gevi Kurniawan; Sutjipto Ngumar; Kurnia Kurnia (JAFFA, 2019)
This study aims to examine the determinants of audit quality, which employs a quantitative method by conducting a survey on 98 public accountants in East Java across of 58 public accounting companies. The findings indicate that audit fee, independence and competence affect audit quality. However, there is no effect of time budget pressure on audit quality, which indicates that the auditors have tendency to maintain audit quality even under time budget pressure.